Interleukin-15 dendritic cells as vaccine candidates for cancer immunotherapy - Anguille, Sébastien (Landes Bioscience, 2013)
Owing to their professional antigen-presenting capacity and unique potential to induce tumor antigen-specific T cell immunity, dendritic cells (DCs) have attracted much interest over the past decades for therapeutic vaccination against cancer. Clinical trials have shown that the use of tumor antigen-loaded DCs in cancer patients is safe and that it has the potential to induce anti-tumor immunity which, in some cases, culminates in striking clinical responses. Unfortunately, in a considerable number of patients, DC vaccination is unable to mount effective anti-tumor immune responses and, if it does so, the resultant immunity is often insufficient to translate into tangible clinical benefit. This underscores the necessity to re-design and optimize the current procedures for DC vaccine manufacturing. A new generation of DC vaccines with improved potency has now become available for clinical use as a result of extensive pre-clinical research. One of the promising next-generation DC vaccine candidates are interleukin (IL)-15-differentiated DCs. In this commentary, we will compile the research data that have been obtained by our group and other groups with these so-called IL-15 DCs and summarize the evidence supporting the implementation of IL-15 DCs in DC-based cancer vaccination regimens.